ANALISIS HASIL BELAJAR BIOSTATISTIKA BERDASARKAN METODE PEMBELAJARAN LURING DAN DARING - I Gede Purnawinadi (Seminar Nasional Official Statistics, 2020)
The current COVID-19 pandemic situation not only affects global health conditions but a very significant impact also occurs in the world of education. The conventional offline learning process switches to online due to conditions that do not allow face-to-face teaching and learning processes to be carried out directly which of course affects the learning outcomes of students. This study aims to analyze the learning outcomes of the biostatistics subject through a comparative test of final semester scores before and during the pandemic at a private university in North Sulawesi. Final grade data from 228 even semester students for the 2018-2019 and 2019-2010 academic years were collected with access through the researcher's account in the information system of private tertiary institutions where this research was carried out then the data was stored in excel form. Data were analyzed through non-parametric statistical Mann-Whitney U-test through the SPSS application that was installed on the computer. The results showed descriptively that the median final score of the semester in the biostatistics course of students with offline and online learning methods was the same, namely 84%, even the bivariate analysis found that the value of p = 0.445> 0.05, which means that at 5% alpha there was no difference between values. the end of the student semester using offline and online methods. Advances in technology and the concept of independent learning allow students to be more active and freer to learn independently through online methods so that the learning process during the pandemic does not have a negative impact on learning outcomes compared to learning conditions through the offline method before the pandemic.